Where does the carbon go? A new carbon balance method to assess what happens to plastics under solar exposure - Gustave Bertier; Arnaud Martel; Matthieu George; Pascale Fabre; Fabien Boucher; Justine Gérome; Fabienne Lagarde (PLoS ONE, 2025)
Plastic pollution is a major and global threat to ecosystems and human health, resulting from the spreading and breakdown of plastic litter in the environment. In an aquatic environment, the first causes of this degradation are exposure to natural ultraviolet light and abrasion or collisions in the water. The extent of such degradation on a plastic object after a given time remains very difficult to quantify, especially regarding the relative production of microplastics, nanoplastics and soluble species along with volatile compounds. All of these degradation products may contribute differently to environmental pollution. Therefore, when evaluating the pollution caused by plastic objects, we should consider how much of each byproduct is generated. We propose a novel method based on conservation of the carbon mass during the degradation process. This approach is the first to enable quantification of carbon retrieved in each type of degradation product (Microplastics, Nanoplastics, Solubles, Volatile Compounds), as well as its evolution with exposure time. By applying this method to polypropylene granules, we demonstrate its effectiveness in tracking carbon footprint throughout the aging process. One of the unexpected results of this study is to show that the amount of carbon released in volatile form is far from negligible (17%) compared to MP (55%). The procedure we present is general enough to be applied to any type of polymer, and can be a valuable tool for assessing the amount of by-products of a given size released into the environment.